Private security – public security (Academic Journal of Internal Affairs, 2023)
Aim: To demonstrate that a market economy based on private property necessarily calls for the services of asset protection companies, which are essential for the dynamic and innovative development of the economy.Methodology: The historical background up to the period of the regime change was supportive for the elaboration of the topic, which was complemented by a dogmatic analysis of the public law-private law dichotomy and the presentation of the body of law regulating private security.Findings: Private security firms are an essential part of an economy based on respect for private property, freedom of contract and equality before the law, but they are also essential to public safety.Value: The arenas of private enterprise and public life in a constitutional state governed by the rule of law serve the common interests of society and the well-being of individuals when security is created collectively by a community of free men.
Keywords: private security; public security; asset protection; market economy